Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsnano.2c05408
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Supplementation Targeting Tumor-Killing Immune Cells Reconstructs the Tumor Microenvironment and Enhances the Antitumor Immune Response

Abstract: The tumor microenvironment (TME) is characterized by several immunosuppressive factors, of which weak acidity and l-arginine (l-arg) deficiency are two common features. A weak acidic environment threatens the survival of immune cells, and insufficient l-arg will severely restrain the effect of antitumor immune responses, both of which affect the efficiency of cancer treatments (especially immunotherapy). Meanwhile, l-arg is essential for tumor progression. Thus, two strategies, l-arg supplementation and l-arg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…As a proof of concept for enantiomer recognition, l -/ d -Arg was used as the target analyte to evaluate the chiral-sensing performance of the self-powered chip and elucidate its mechanism. Arg is necessary for cell division, brain chemistry, immune responses, blood vessel dilation, and neurotransmission d -Arg has significant pharmacological activities in mammals …”
Section: Resultsmentioning
confidence: 99%
“…As a proof of concept for enantiomer recognition, l -/ d -Arg was used as the target analyte to evaluate the chiral-sensing performance of the self-powered chip and elucidate its mechanism. Arg is necessary for cell division, brain chemistry, immune responses, blood vessel dilation, and neurotransmission d -Arg has significant pharmacological activities in mammals …”
Section: Resultsmentioning
confidence: 99%
“…Further studies, ideally exploring more cytokines and chemokines, are warranted to dissect how exactly L-Arginine is able to modulate their circulating levels. Potential mechanisms by which L-Arginine exerts anti-inflammatory effects may include the reconstitution of circulating L-Arginine levels, a correction of nitric oxide dysfunction, and/or a direct action on immune cells [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] .…”
Section: Discussionmentioning
confidence: 99%
“…163 Similarly, Zhang et al reported a multivesicular liposome capable of both supplying L-arginine to the acidic TME and blocking cationic amino acid transporter 2 (CAT-2) with shRNA, which increased the amount of tumor infiltrating CD8 + T cells and sensitized ICB therapy with anti-PD-L1. 164 Targeting key enzymes in the metabolic pathways of various nutrients is a more common strategy to inhibit endogenous nutrient consumption. The diversity and plasticity of nanotechnologies allow such goals to be achieved at protein or gene levels.…”
Section: Nanotechnology-mediated Reprogramming Of Metabolism For Enha...mentioning
confidence: 99%